The Degree of Implementation of Mathematics Teachers to Global Process Standards According to NCTM in the Primary Education Level in Qatar - Al-sarha, Ebtehal Qaid; Barham , Areej Isam (Dirasat: Educational Sciences, 2023)
Objectives: The current study aimed to measure the degree to which mathematics teachers employ international operational standards according to NCTM in primary education classes in the State of Qatar. Methods: To achieve the objectives of this study, the descriptive analytical method was used. The observation card tool was applied to a sample of 50 female mathematics teachers, who were randomly selected from 16 schools by stratified random sample. To collect the data, the class observation card was used, and its’ validity was verified by presenting it to a group of specialized arbitrators. The reliability was calculated by using the observers’ agreement method (Cooper’s equation). The percentage of agreement between the observers ranged between (78%-92%). The stability of the tool was also verified by using (measure of internal consistency), and it was found that the value of the stability coefficient of the tool was (93.6%). Results: The results of the quantitative analysis showed that the degree of mathematics teachers’ implementation of process standards in the primary education classes was low for Problem-Solving standard, Reasoning and Proof standard, Connection standard, and Representation standard, while it was moderate for the Communication standard. Conclusions: Providing courses and training In the light of the study’s results workshops to develop the teaching practices of math teachers at the primary level in the standards that were employed (low) which are Problem-Solving, Mathematical Reasoning and Proof, Mathematical Connection, and Mathematical Representation.